(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Two major issues that compromise the integrity of legal systems are malicious prosecution and miscarriages of justice. Malicious prosecution is the act of bringing legal action without a valid reason and with the intention of causing the accused unnecessary harm. On the other hand a miscarriage of justice is when the legal system makes mistakes that lead to the punishment of innocent people. Wide-ranging repercussions result from both problems such as diminished public confidence in the legal system as well as emotional monetary and reputational harm to those concerned. The main concepts legal terminology and case law pertaining to malicious prosecution and miscarriage of justice are examined in this essay. It looks at the connections between these two problems which frequently result in structural breakdowns that prevent fair trials. It also covers the difficulties in demonstrating malicious intent and procedural mistakes. This paper seeks to demonstrate the significance of accountability transparency and fairness in legal procedures in order to stop these injustices and shield people from harm by evaluating case studies and making reform recommendations.